2020
DOI: 10.21037/apm.2020.03.17
|View full text |Cite
|
Sign up to set email alerts
|

The mysteries of rapidly destructive arthrosis of the hip joint: a systemic literature review

Abstract: Rapidly destructive arthrosis (RDA) is considered a rare and poorly diagnosed disease but is now seen more frequently in practice due to ageing populations. The most typical radiological features are flat femoral heads, absence of articular cartilage, subchondral bone destruction and signs of joint effusion.These features could be found on X-ray or magnetic resonance imaging (MRI). Surgeons should consider the presence of RDA when patients show rapid femoral head destruction. The purpose of this study is to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 43 publications
1
13
0
4
Order By: Relevance
“…Overall, these findings are consistent with the diagnosis of RDA. A systematic review of RDA reported that the risk factors for this condition were the female sex and age >60 years [12], consistent with the present case.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, these findings are consistent with the diagnosis of RDA. A systematic review of RDA reported that the risk factors for this condition were the female sex and age >60 years [12], consistent with the present case.…”
Section: Discussionsupporting
confidence: 90%
“…Including the history of trauma in the diagnostic criteria of RDA remains controversial [ [12] , [13] , [14] ]. Our patient had a normal hip without osteoarthritis before the injury, and the destruction of the hip joint had been triggered by an acetabular fracture.…”
Section: Discussionmentioning
confidence: 99%
“…La CDR prédomine chez la femme (60-90 %), plutôt âgée (âge moyen de 72 ans vs 61 ans chez l'homme, jamais avant 45 ans), de topographie unilatérale (80-90 %), parfois bilatérale [1,2,4]. Les facteurs de risque, en dehors de l'âge et du sexe féminin, sont l'obésité, la surcharge mécanique, les traumatismes de type indirect (chute, grand écart) ou direct (fracture acétabulaire rencontrée dans 6 % des ADRP) [2,3,5].…”
Section: Arguments Cliniques 21 Hancheunclassified
“…Les ostéoclastes jouent un rôle important dans la résorption osseuse, présents dans la synoviale, dans le tissu de granulation hypervascularisé et sont plus nombreux dans l'ADRP que dans l'arthrose commune, notamment dans les zones actives ; la CDR est associée à une augmentation du taux du taux des molécules favorisant la résorption osseuse (IL-6, IL-1, métalloprotéinases). L'endothélium pourrait jouer un rôle important dans le recrutement des précurseurs des ostéoclastes sur les sites de résorption [5].…”
Section: Rôle Des Ostéoclastesunclassified
See 1 more Smart Citation